MOVEMENT OF CURRENT AND EXPECTED INFLATION IN THE EUROZONE - Srzentić, Miloš (Economic Outlook, 2024)
Analysis of movement of inflation and unemployment in the observed period in the Eurozone makes the basic object of this paper. The aim of this paper is to be determined whether аrе and up to which measures movements of relation of inflation and unemployment, represented with considered concepts of the Phillips curve, of importance for sustaining of economic system as a whole, or their parts. As a factor which indirectly influences on a movement of economic sizes represented with the Phillips curve it is considered an influence of relation of export and import instead of influence of unemployment. In order to be accomplished that analyses, the basic hypothesis, which will be examined in this paper, is formulated on the following way: as is bigger a relation of possibility of export and import that is bigger a possibility of sustaining inflation on the aimed level. For collecting and classification of data of movement of observed macroeconomic sizes in this paper is used a method of quantitative analysis. Methods of scientific research which were used for analyzing of theoretical concepts of the Phillips curve are a method of qualitative analysis and a comparative method.